2003
DOI: 10.1002/er.870
|View full text |Cite
|
Sign up to set email alerts
|

Shock tube pyrolysis of thiophene

Abstract: SUMMARYThe kinetics of the thermal decomposition of thiophene diluted in argon have been studied behind reflected shock waves in a single pulse shock tube over the temperature range 1598-2022 K and pressures between 2.5 and 3.44 bar. Product yields and composition were determined using capillary column gas chromatography with flame ionization detection and flame photometric sulphur selective detection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
19
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(22 citation statements)
references
References 8 publications
3
19
0
Order By: Relevance
“…As illustrated in the introduction, earlier studies suggested that pyrolysis of thiophene is triggered by the C–S fission and quantum chemical calculation indicated that α-H migration to S site is more likely to occur compared to C–S fission. In this paper, this discussion was also introduced in benzothiophene pyrolysis mechanism. The possible initial reaction steps of benzothiophene pyrolysis can be mainly divided into two groups: bond rupture and H­(proton)-migration.…”
Section: Resultsmentioning
confidence: 89%
See 1 more Smart Citation
“…As illustrated in the introduction, earlier studies suggested that pyrolysis of thiophene is triggered by the C–S fission and quantum chemical calculation indicated that α-H migration to S site is more likely to occur compared to C–S fission. In this paper, this discussion was also introduced in benzothiophene pyrolysis mechanism. The possible initial reaction steps of benzothiophene pyrolysis can be mainly divided into two groups: bond rupture and H­(proton)-migration.…”
Section: Resultsmentioning
confidence: 89%
“…It is known that quantum chemical calculation plays a major role in chemical reaction mechanism study. Earlier studies, relying on experiment, suggested that pyrolysis of thiophene is triggered by the C–S fission. However, recent studies using quantum chemical calculation, indicated that α-H migration to S site is more likely to take place compared with C–S fission. Hence quantum chemical research on benzothiophene pyrolysis behavior is necessary to promote the understanding of pyrolysis mechanism.…”
Section: Introductionmentioning
confidence: 99%
“…e mechanism by which thiophenes burn remains unclear. e early studies on the combustion of thiophene were mainly carried out by experiments [20][21][22][23][24], and the combustion products detected were mainly alkynes, H 2 S and CS 2 .…”
Section: Combustion Experimentationmentioning
confidence: 99%
“…Zhao et al [243] conducted a series of pyrolysis on inorganically desulfurized coals at temperatures ranging from 673 K to 1173 K. They observed that most of the organic sulfur escaped as H 2 S. Calkins [244] conducted pyrolysis of raw and pyrite removed Pittsburgh #8 coal in a pyroprobe GC/MS at temperatures of 523-1273 K. He observed H 2 S, COS, CS 2 , CH 3 SH, SO 2 , and mostly thiophene and thiophenic compounds in the gaseous product. Investigations on the pyrolysis of thiophene and thiophenic compounds have concluded that H 2 S is the major compound released [245][246][247][248]. Therefore, it can be concluded that H 2 S is the main compound resulting from pyrolysis of organic sulfur.…”
Section: Effect Of Blending Coal and Biomass/waste On The Fate Of Sulmentioning
confidence: 99%